(3UaGJ GdCUajGA hcQGeGJ GdChdjGA GdefJNH ef MdjI GdChdjGA hZjQg ef GdcJH GdeUfaI aj ebGeGJ GdUGdMjf GdCJbjGAs - (3CHh GdbGSe efUhQ Hf CMeO Hf GdaVd GdefgGLjs
(3ChdgG (B:s
(3Chdg eHJhQ , hjHOC GdehLhO efg CKfGA GdebOeI , Hbhdg , SWhJg hehLHGJ fbeJg , hCeQge HJfajP CMcGeg ai eedcJg s
(3BNQgG (B:s
(3hjfJgi HJQLeI (B" (3CHj GdbGSe GdMcje (B" (3ef Cgd SeQbfO hBNQ eG ajI (B: (3efi Ef Jcf MbkG Jcf CMSf Gdefi hEdG abO YTfG HgG RefkG QZOkG Ke GdcJGH s
(3HChdgG hQbJGf HNW MOjKs
(3GdfSNI ai LRFjfs
(3VegeG eLdO hGMO hbO CKHJfG YfhGf GdcJGH ef HOGjI GdLRA GdKGfi GdPi HkO HGdhQbI (B86s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs